2019
DOI: 10.1017/ice.2019.47
|View full text |Cite
|
Sign up to set email alerts
|

Threatened efficiency not autonomy: Prescriber perceptions of an established pediatric antimicrobial stewardship program

Abstract: Background:Implementing antimicrobial stewardship programs (ASPs) can be challenging due to prescriber resistance. Although barriers to implementing new ASPs have been identified, little is known about how prescribers perceive established programs. This information is critical to promoting the sustainability of ASPs.Objective:To identify how prescribers perceive an established pediatric inpatient ASP that primarily utilizes prior authorization.Methods:We conducted a cross-sectional survey administered from Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…In addition, similar to a prior study of hospitalized medical patients with ASB started on antibiotics by any clinician, we found that patients with ASB who were treated with antibiotics had a longer duration of hospitalization [ 2 ]. Because ASB is common, antibiotics are harmful, and diagnosis momentum makes discontinuing antibiotics challenging [ 37 ], stewardship interventions must target both the initial testing by EM clinicians and the continuation of antibiotics by inpatient clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar to a prior study of hospitalized medical patients with ASB started on antibiotics by any clinician, we found that patients with ASB who were treated with antibiotics had a longer duration of hospitalization [ 2 ]. Because ASB is common, antibiotics are harmful, and diagnosis momentum makes discontinuing antibiotics challenging [ 37 ], stewardship interventions must target both the initial testing by EM clinicians and the continuation of antibiotics by inpatient clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,25 Implementation, maintenance, and growth of successful ASPs require a willingness to understand and have a flexible mindset about certain cultural norms, including those specific to individual hospitals, medical specialties, and to the hierarchical culture of medicine. 27,28 ASPs must concurrently work to promote behavioral modifications leading to improved antimicrobial utilizationand such efforts often require advocating for cultural change. Staff nurses report that some of the greatest barriers to their involvement in AS stem from unit-specific and hierarchical cultural expectations, including inconsistent nursing inclusion during the rounding process and deference to physicians and pharmacists regarding antibiotic management plans.…”
Section: Hospital/local Stewardship Pediatric Nurses As Antimicrobialmentioning
confidence: 99%
“…Again, clinicians did not seem to recognize the harms associated with overtreatment citing the fact that if the patient was doing fine, they would not make adjustments, specifically because doing this would take time. This compares to literature citing concerns with inefficiency and inertia of previous practice [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have shown that ordering urine testing in asymptomatic women leads to unnecessary antibiotics [ 7 , 16 ] and that PSA screening in asymptomatic older men can lead to negative consequences such as harms from biopsies, surgery or radiation treatment, as well as psychological harm [ 17 ]. There is also literature to support that clinicians want to feel like they have done everything for their patients [ 18 ]. Participating physicians seemed to under-weigh the risks of performing the action when discussing how they approach patient care, though acknowledged these risks when specifically asked general knowledge questions.…”
Section: Discussionmentioning
confidence: 99%